Epistfemicidio y transversalidad de género : avances en la reforma del currículum de Abogacía de la Universidad Nacional de Río Negro - Heim, Daniela (2019)
Abstract: The article analyzes the incorporation of the gender perspective in the university curriculum as an equality policy and establishes hermeneutical criteria that make possible the implementation and evaluation of this perspective. It qualifies as "epistfemicide" the absence of women-their knowledge, experiences and proper ways of being, feeling and seeing the world- in curricula and educational processes as a whole. It inquires in two of the proposed strategies to confront the "epistfemicide": the gender specificity and the gender mainstreaming in the university curriculum. Finally, based on the criteria and strategies of reference-and as a case study- it reflects on the curriculum of the Legal career of the National University of Río Negro and its recent reform.